2001
DOI: 10.1007/s11661-001-0197-4
|View full text |Cite
|
Sign up to set email alerts
|

Uniaxial tensile deformation of uranium 6 wt pct niobium: A neutron diffraction study of deformation twinning

Abstract: The deformation of polycrystalline uranium 6 wt pct niobium (U6Nb) was studied in situ during uniaxial tensile loading by time-of-flight neutron diffraction. Diffraction patterns were recorded at incremental stresses to a maximum of 450 MPa (ϳ4 pct macroscopic strain). Consistent with reorientation of the martensite variants by twinning, significant changes in the diffraction peak intensities, which were proportional to the plastic contribution of the macroscopic strain, were observed. Both the lattice paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 32 publications
5
48
0
Order By: Relevance
“…[1]. That twins result in significant strain hardening, in this case, only at strains beyond the plateau region, is well established in the metallurgical literature, in general, [58,59] and in Mg, in particular. [16,20,25,28,33,60] The relationship between the plateau and twinning is further enhanced by noting that neither Co [34] nor Ti 3 SiC 2 twin; neither exhibit a plateau.…”
Section: A Knementioning
confidence: 83%
See 1 more Smart Citation
“…[1]. That twins result in significant strain hardening, in this case, only at strains beyond the plateau region, is well established in the metallurgical literature, in general, [58,59] and in Mg, in particular. [16,20,25,28,33,60] The relationship between the plateau and twinning is further enhanced by noting that neither Co [34] nor Ti 3 SiC 2 twin; neither exhibit a plateau.…”
Section: A Knementioning
confidence: 83%
“…The role of twinning in hardening is well appreciated in the metallurgical literature. [16,20,25,28,[58][59][60] When Agnew et al [24] studied the two other orientations, viz. IPT and TTC (Figures 2(a) and (c)), respectively, they found that twinning played a much more modest role in the deformation, especially at low deformation strains.…”
Section: B Correlation Between Kinking Bending and Twinningmentioning
confidence: 99%
“…For example, the related polymer polyethylene is employed for neutron moderation at the LANSCE facility (for a discussion of the forms of polyethylene see [3]). Previous applications of SMARTS have been focused on metallic materials (see for example [4][5][6][7][8][9]). This is partially due to difficulties in interpreting diffraction patterns of amorphous materials [10], and partially because of the relatively few polymers that could be successfully probed in the bulk by diffraction methods.…”
Section: Introductionmentioning
confidence: 99%
“…Amorphous PTFE has the same repeat atomic structure as the crystalline domains but without significant order. The extreme molecular weight of PTFE (∼1×10 6 ), allows a given polymer chain to assemble in both amorphous and crystalline regions [18].…”
Section: Introductionmentioning
confidence: 99%
“…[1,2,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] These reports were generated using a combination of four processes: optical microscopy, transmission electron microscopy (TEM), neutron diffraction, and automated electron backscatter diffraction (ESBD). Optical microscopy can only identify probable twins using grain shape as the sole criteria.…”
Section: Introductionmentioning
confidence: 99%